Sistem pemasaran dan bagi hasil pada crew kapal pancing ulur (hand line) Kota Kendari - Mursiq, Sa'adilal; Yusuf, Sarini; Riani, Irdam; Ishak, Ermayanti; Arami, Hasnia; Sriwulan, Desy (Universitas Halu Oleo, 2024)
Hand line is fishing method that is commonly used to catch skipjack and yellowfin tuna. The marketing and revenue-sharing system may affect the welfare of the crew. This study aims to determine the marketing and revenue sharing system of hand line fishermen in Kendari in March 2022. The research sample consisted of 3 fishermen who owned the boat that was selected by purposive sampling method. The three hand line boats were KM KRS 01 with a capacity of 20 GT, KM Armadana at 5 GT and KM Cahaya Saindo at 9 GT. Data were obtained through interviews using structured questionnaires. The data were analyzed using a descriptive qualitative analysis. The study showed that ship owners marketed the fish through collecting merchants, then collecting merchants to retailers or companies. The income of the three ships in one fishing trip was varies. The income for one fishing trip at KM KRS 01 wasIDR 32,500,000, KM Armadana was IDR 18,500,000 and KM Cahaya Saindo was IDR 18,000,000. The owner of the ship in this study was also a captain. The ship owner gets the same share as the crew, which is 50% of the total catch each. Captain also got a division in the crew share with an even division among all crew members regardless the type of work and rank in the ship. The marketing and profit-sharing system in this study is more beneficial to ship owners so improvements are needed by shortening the supply chain and a more equitable profit-sharing system.